Pendidikan Anak Usia Dini dalam Domain Pemimpin Gereja - Priska Manullang (Institut Agama kristen Negeri Tarutung, 2021)
Abstract Early Childhood Education in the domain of church leaders is Early Childhood Education which receives convenience from the domain of church leaders. Early Childhood Education included in the domain of church leaders is formal Early Childhood Education and Non-Formal Early Childhood Education. The basis of this paper is first: The domain of church leaders towards formal Early Childhood Education is in the achievement of quality map instrument standards and child pride standards in child development reports. Second: The domain of church leaders towards non-formal Early Childhood Education is in improving the competence of Sunday school teachers and fundraising or becoming donors in the implementation of Sunday school activities. So formal and non-formal Early Childhood Education is hopeful in the domain of church leaders. Should be, because it is based on biblical teachings, church leaders also hope to be able to smell formal and non-formal Early Childhood Education. Keywords: Early Childhood Education, Church Leaders, domains Abstrak Pendidikan Anak Usia Dini dalam domain pemimpin gereja adalah Pendidikan Anak Usia Dini yang menerima kemudahan dari domain pemimpin gereja. Pendidikan Anak Usia Dini yang termasuk dalam domain pemimpin gereja ialah Pendidikan Anak Usia Dini formal dan Pendidikan Anak Usia Dini non formal. Dasar dari hasil tulisan ini ialah pertama: Domain pemimpin gereja terhadap Pendidikan Anak Usia Dini formal ialah dalam pencapaian standar instrumen peta mutu dan standar perkemabangan anak dalam laporan perkembanagan anak. Kedua: Domain pemimpin gereja terhadap Pendidikan Anak Usia Dini non formal ialah dalam peningkatan kompetensi guru sekolah minggu dan penggalangan dana atau menjadi donatur dalam pelaksanaan kegiatan sekolah minggu. Jadi Pendidikan Anak Usia Dini formal dan non formal berharap dalam domain pemimpin gereja. Seyogianya, karena didasari ajaran Alkitab, pemimpin gereja juga berharap agar dapat berdomaian terhadap Pendidikan Anak Usia Dini formal dan non formal. Kata Kunci: Pendidikan Anak Usia Dini, Pemimpin Gereja, domain